PERBANDINGAN KOMUNITAS KUPU-KUPU PADA BERBAGAI TIPE, KARAKTERISTIK, DAN GANGGUAN LINGKUNGAN HUTAN KOTA - Siva Devi Azahra; Burhanuddin Masy'ud; Noor Farikhah Haneda (Department of Forest Resources Conservation and Ecotourism - IPB University, 2016)
Butterfly has many ecological roles and it can be found in a wide range of habitats in urban areas. Urban forest as one of the butterfly habitat in urban areas has high conservation value, in contrast, environmental disturbances have been indicated causes various changes in urban forest environmental condition and affect communities that exist within it, including butterfly. This research aims to compare and analyze butterfly communities in various types, characteristics, and environmental disturbances of urban forest. The surveys were carried out at four types of urban forest (residential, industrial, recreational,and highway types) in East Jakarta Municipality on three different periods (dry, dry-wet transitional, and wet seasons) from October 2014 to Januari 2015 by using Pollard Transect method. Study showed that butterfly diversity was decreasing within increasing degree of environmental disturbance. Transitional period and urban forest in residential area had the highest species richness and diversity, moreover, recreational and residential types of urban forest had the highest community similarity in all seasons. Keywords: butterfly, characteristic, environmental disturbance, types, urban forest